2022
DOI: 10.1590/1519-6984.245813
|View full text |Cite
|
Sign up to set email alerts
|

Serological prevalence of hepatitis B virus (HBV) in Mardan district, Khyber Pakhtunkhwa, Pakistan

Abstract: Hepatitis B virus infection is perilous among the five types of Hepatitis, as it remains clinically asymptomatic. The present study draws up-to-date prevalence of Hepatitis B virus (HBV) in the general population of Mardan, Khyber Pakhtunkhwa Pakistan. The blood samples from 4803 individuals including 2399 male and 2404 females were investigated. All the suspected samples were analyzed for hepatitis B surface antigen using Immuno-chromatographic test (ICT), Enzyme-linked immunosorbent assay (ELISA), and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…The prevalence of hepatitis B infected population was higher in men 70.52% (95% CI 68.65-72.32) than women 29.48% (95% CI 27.68-31.35) in our population. (Table 3.1.1) Similar to our findings, higher prevalence in men than women were reported by Ullah , et al 10 (61.23% vs. 38.77% ), Khan, et al 9 from Mardan, Pakistan (56.92% vs. 43.08%), Khan, et al 7 from Lahore, Pakistan (68.15% vs. 31.85%), Mousawea , et al 6 (79.01% vs. 20.99%), Tao, et al 5 (58.53% vs. 41.47%), Soliman, et al 4 (67.25% vs. 32.75 %) & Badawi, et al 3 (77.81% vs. 22.19%). Dissimilar to our findings, lower prevalence in men than women were delineated by Ullah, et al 8 from Peshawar, Pakistan (38.46% vs. 61.54%).…”
Section: Distribution Of Hepatitis B Infected Population By Sex (H 01 )supporting
confidence: 91%
“…The prevalence of hepatitis B infected population was higher in men 70.52% (95% CI 68.65-72.32) than women 29.48% (95% CI 27.68-31.35) in our population. (Table 3.1.1) Similar to our findings, higher prevalence in men than women were reported by Ullah , et al 10 (61.23% vs. 38.77% ), Khan, et al 9 from Mardan, Pakistan (56.92% vs. 43.08%), Khan, et al 7 from Lahore, Pakistan (68.15% vs. 31.85%), Mousawea , et al 6 (79.01% vs. 20.99%), Tao, et al 5 (58.53% vs. 41.47%), Soliman, et al 4 (67.25% vs. 32.75 %) & Badawi, et al 3 (77.81% vs. 22.19%). Dissimilar to our findings, lower prevalence in men than women were delineated by Ullah, et al 8 from Peshawar, Pakistan (38.46% vs. 61.54%).…”
Section: Distribution Of Hepatitis B Infected Population By Sex (H 01 )supporting
confidence: 91%
“…The present study was designed to determine the rate of intra-familial HBV transmission either horizontal (Spouse transmission) or vertical transmission (Parents to children) in a model community population. The study was limited to a predefined model research village and among parents having children, therefore the reported HBV prevalence of 1.5% among married couples was found comparatively lower than the actual prevalence of HBV in Pakistan 2-8% (13,14). The assumption of HBV index cases (37 index families) was calculated initially for this study was also based on the prevalence of HBV (15).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, between 1.2% and 15.9% of people have HCV (5). In Pakistan, the frequency of hepatitis B infection is alarmingly rising, ranging from 2 to 8% in various populations.20.2% of the district is urban, while 79.8% of the region is rural 10 . Hepatitis B and C in pregnant females: Millions of people worldwide die each year from viral hepatitis, even pregnant women.…”
Section: Fig 2: Development Of Hbv Infectionmentioning
confidence: 99%